Wireless sensor networks routing algorithm based on particle swarm optimisation. (2018) - Yang, Junhan
Routing policy is a key problem in wireless sensor network (WSN), and it aims to find an optimal path to transmit the data of source nodes to the destination nodes. Wireless sensor networks can represented as a graph model, where graph nodes refers the wireless sensors, and graph edges are used to connects various sensors. Furthermore, in this work, we suppose that wireless sensor networks contain three types of nodes, including base station, gateway, and sensor. In the proposed algorithm, each particle is exploited to provide a suitable route from each cluster head to the base station, and the dimension of each particle is equal to the number of gateways in WSN. In the end, experimental results demonstrate that the proposed algorithm is able to effectively prolong network lifetime and increase the number of packets received by base station. Furthermore, the conclusion can be drawn that the proposed method can effectively solve the WSN's routing problem, because particle swarm optimisation is able to effectively optimise WSN routing scheme.